Religious Radicalism Demarcations and Challenges - Temmerman, Johan (ASP editions - Academic and Scientific Publishers, 2021)
"Religious Radicalism scrutinizes the religious motives and mechanisms of radicalism. The contributors observe a growing lack of understanding of religion in secular policy-bodies, as well as in the academic world in Europea and beyond. They put forward an approach 'from within' and aim to provide policy-makers with workable tools and a user-friendly method for constructively tackling religious radicalism. The underlying issue is the question of the role of the rule of law in relation to human rights in relation to religious minorities. This edited volume brings forward an interdisciplinary approach to religious radicalism blending religious studies, theology, and cultural criticism. Above all Religious Radicalism is an invitation for dialogue and a plea for understanding. In the current polarized cultural climate it is delicate to ask for prejudices to be avoided. We can tend to think that the 'other' has to trust us, and that change applies to those who think and feel differently than we do. Increasing illiteracy is both a cause and effect of religious radicalism. Those who do not feel understood and recognized and whose identity is systematically discredited turn against the institutional powers that leave the offence untouched. In short, radicalism is threatening. But for those who are completely alien to customs and backgrounds, symbols and behavior, the unprecedented and unfamiliar are just as much of a threat. This form of radicalism, which is rapidly rising on wings of ignorance, also calls for self-criticism."